1993
DOI: 10.1002/mus.880160404
|View full text |Cite
|
Sign up to set email alerts
|

The estimated numbers and relative sizes of thenar motor units as selected by multiple point stimulation in young and older adults

Abstract: Multiple point stimulation (MPS) is described as a method of estimating the numbers of motor units in the median innervated thenar muscles of young and older control subjects. Stimulation at multiple sites along the course of the median nerve was employed to collect a sample of the lowest threshold, all-or-nothing surface-recorded motor unit action potentials (S-MUAPs). The average, negative peak area, and peak-to-peak amplitude of the sample of S-MUAPs was determined and divided into the corresponding value f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
176
1
5

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(206 citation statements)
references
References 22 publications
24
176
1
5
Order By: Relevance
“…In addition to a disregulation of hormonal homeostasis, an elevation of inflammatory activity and TNF-␣ signaling (16) has also been suggested to contribute to sarcopenia. Furthermore, in humans and rodents, it has been observed that, with age, neuromuscular communication becomes dysfunctional, spinal cord motor neurons die, and motor units are lost (3,6,19). In rats this has been reported to lead to an increased incidence of denervation (28).…”
mentioning
confidence: 99%
“…In addition to a disregulation of hormonal homeostasis, an elevation of inflammatory activity and TNF-␣ signaling (16) has also been suggested to contribute to sarcopenia. Furthermore, in humans and rodents, it has been observed that, with age, neuromuscular communication becomes dysfunctional, spinal cord motor neurons die, and motor units are lost (3,6,19). In rats this has been reported to lead to an increased incidence of denervation (28).…”
mentioning
confidence: 99%
“…This overlap results in stimulus-tostimulus alternation of the axons excited with a constant stimulus Milner-Brown and Brown 1976). There is no evidence for a systematic relationship between threshold and motor axon diameter using percutaneous stimuli in human nerves (Doherty and Brown 1993;Doherty and Stashuk 2003). Therefore in the model, axon thresholds were randomly associated with motor unit twitch forces.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Once the lowest threshold SMUPs had been collected, the stimulator was moved approximately 15 mm along the nerve trunk. This distance was so chosen because, beyond that, the risk of inadvertently activating the same SMUPs is negligible (Doherty and Brown, 1993). After all SMUPs were collected (i.e., no additional SMUPs were observed at either stimulus pulse width), the program averaged the SMUPs in a "data point by data point" manner.…”
Section: Motor Unit Number Estimationmentioning
confidence: 99%
“…Motor unit number estimation (MUNE) is a neurophysiological method that can help to define the severity, follow the progression and detect the efficacy of treatment of neuromuscular diseases, in which motor neuronal or axonal loss is a major feature (Doherty and Brown, 1993;Simmons et al, 2001). There are a variety of MUNE techniques, most of which derive the estimate of motor units from the ratio of the maximum compound muscle action potential (CMAP) to the average surface motor unit action potential (SMUP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation